Engineering a career in agriculture and food - Samsuzana, Abd Aziz, Dr.; Azmi, Yahya, Ir. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.my/